ANALISA PEMELIHARAAN PREVENTIF ALAT ULTRASONOGRAPH (USG) SIEMENS AQUSON-X300 DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - Pardosi, Putra Jaya; Primasyukra, Mhd.Aldi; Ulina, Sri; Abdillah, Khairil (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2024)
Ultrasonograph (USG) is a diagnostic support tool in hospitals, which utilizes ultrasonic waves with a frequency (more than 20,000 Hz) to produce images. This tool is needed for parents, especially pregnant women, to find out the condition / development of the fetus. Preventive or preventive maintenance is maintenance activities in the form of maintenance by cleaning tools which are carried out every day by operators and adjustment, lubrication and replacement of maintenance materials which are carried out by technicians on a regular basis. The method used in this research is observation with qualitative descriptive research. Based on the results of the research on the preventive maintenance of the Ultrasonograph (USG) device at the University of North Sumatra Hospital in Medan, where out of the 20 questions given, 17 answered yes and 3 answered no, thus the implementation of preventive maintenance at the North Sumatra General Hospital was concluded as good.